Ecosystem Model of Edu-Tourism for Organic Waste Conversion in Islamic Boarding Schools through Maggot Cultivation - Dzikrulloh Dzikrulloh; Alan Suud Maadi; Tri Pujiati (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2023)
The purpose of this research is to determine the relationship between the Edu-Tourism Ecosystem Model of Organic Waste Conversion in Islamic Boarding Schools and maggot cultivation. This research began by finding a picture of waste processing in Islamic boarding schools, which was further developed by analyzing the feasibility of business and waste processing management. The results of this study offer the concept of eduwisata maggot-based organic waste processing in Islamic boarding schools.This research is qualitative, using a study-case approach, with the object of research being the Islamic Boarding School in Bangkalan, which has at least 1,000 students. There are five Islamic boarding schools that meet the criteria: Al Aziziyah, Asshomadiyah, Nurul Kholil, Shaikhona Kholil, and Nurul Amanah. According to the study's findings, the results of the business feasibility analysis produced positive value both economically, technically, and, to the greatest extent possible, in marketing. The feasibility analysis of the business needs to be supported by good processing management through planning, organizing, actuating, and controlling. Furthermore, the concept of maggot-based organic waste treatment (eduwisata) is integrated by combining tutorial learning activities with on-site exploration activities.